First report of an economically important genus Euscelidius (Cicadellidae: Deltocephalinae: Athysanini) from the Indian subcontinent, with description of a new species - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2020)
The economically important genus Euscelidius Ribaut, 1942 is reported first time from the Palearctic temperate coniferous forests and montane grasslands and shrublands of Pakistan with the new species Euscelidius cornix sp. nov. Photographic illustrations and a description are provided for the habitus and male genitalia. A key and aedeagal illustrations are provided to distinguish all the species of the genus Euscelidius Ribaut worldwide along with their distribution.